Engaging and developing front-line clinical nurses to drive care excellence: Evaluating the Chief Nurse Excellence in Care Junior Fellowship initiative - Bramley, Louise (J Res Nurs, 2018)
BACKGROUND: Global challenges in the development of a highly skilled and motivated nursing workforce jeopardise the delivery of high-quality care. Flexible and innovative workforce solutions are required to overcome these challenges. AIMS: To describe the implementation and present the preliminary evaluation of the ‘Chief Nurse Excellence in Care Junior' bespoke Fellowship initiative designed to develop the foundational clinical and academic skills of front-line junior clinical staff. METHODS: This initiative was developed and piloted at a large, inner-city, acute NHS trust. The initiative involved two main components: a bespoke development programme and an improvement project that was supported by clinical and academic mentors. The initiative was evaluated using structured feedback, case studies and data on dissemination activities. RESULTS: Six front-line nurses completed the first cohort of the initiative that commenced in spring 2016. Results showed a positive impact on professional development relating to the acquisition of new knowledge and skills. Case studies of projects had a demonstrable impact on patient experiences, outcomes and cost savings. Wider organisational and NHS impact was demonstrated through multiple dissemination activities. CONCLUSION: This preliminary evaluation provides evidence that this initiative is a sustainable, clinically driven career development opportunity at a foundational level that has a demonstrable positive impact on care and staff development. Further work is underway to carry out a longitudinal structure, process and outcome evaluation with particular focus on impact.